Evaluation of plaque stability of advanced atherosclerotic lesions in apo E-deficient mice after treatment with the oral factor Xa inhibitor rivaroxaban - Zhou, Qianxing; Bea, Florian; Preusch, Michael; Wang, Hongjie; Isermann, Berend; Shahzad Hussain, Khurrum; Katus, Hugo; Blessing, Erwin (Mediators of inflammation, 2011)
Aim. Thrombin not only plays a central role in thrombus formation and platelet activation, but also in induction of inflammatory processes. Activated factor X (FXa) is traditionally known as an important player in the coagulation cascade responsible for thrombin generation. We assessed the hypothesis that rivaroxaban, a direct FXa inhibitor, attenuates plaque progression and promotes stability of advanced atherosclerotic lesions in an in vivo model. Methods and Results. Rivaroxaban (1 or 5 mg/kg body weight/day) or standard chow diet was administered for 26 weeks to apolipoprotein E-deficient mice ( per group) with already established atherosclerotic lesions. There was a nonsignificant reduction of lesion progression in the high-concentration group, compared to control mice. FXa inhibition with 5 mg Rivaroxaban/kg/day resulted in increased thickness of the protective fibrous caps (12.3 ± 3.8 μm versus 10.1 ± 2.7 μm; P < .05), as well as in fewer medial erosions and fewer lateral xanthomas, indicating plaque stabilizing properties. Real time-PCR from thoracic aortas revealed that rivaroxaban (5 mg/kg/day) treatment reduced mRNA expression of inflammatory mediators, such of IL-6, TNF-α, MCP-1, and Egr-1 (P < .05). Conclusions. Chronic administration of rivaroxaban does not affect lesion progression but downregulates expression of inflammatory mediators and promotes lesion stability in apolipoprotein E-deficient mice.
Gesehen am 19.01.2023